The Origins of Evolutionary Innovations : A Theory of Transformative Change in Living Systems - Wagner, Andreas, 1967 January 26- (Oxford, New York Oxford Univ. Press, 2011)
Every organism has visible, macroscopic traits that represented dramatic, transformative innovations when they first arose, changing not only organismal lifestyles, but also the future evolutionary path of life. This book provides the first major synthesis of existing knowledge that will form the basis of a theory of innovation in living systems
Include Index
Keywords: Evolution (Biology) -- Genetic transformation -- Biology--Philosophy